Circular RNAs: a new frontier in the study of human diseases. Issue 6 (3rd March 2016) - Chen, Yonghua; Li, Cheng; Tan, Chunlu; Liu, Xubao
Abstract : Circular RNAs (circRNAs) are recently discovered new endogenous non-coding RNAs and an area of much research activity. In addition to their potential as major gene regulators, reports are linking heterogeneous circRNA groups with many different human disorders, especially cancer. In this review, we focus on the rapidly advancing field of circRNAs that play a part in human diseases. We list tools (eg, public databases) that scan genome spans of interest to identify known circRNAs; describe the relationship between dysregulated circRNAs and human disease, highlighting their specific roles; and consider the possible use of current and potential circRNA research applications in treating human diseases. Specifically, we review the role of circRNAs as biomarkers, drug targets and therapeutic agents.